2010
DOI: 10.2967/jnumed.109.073411
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Adenosine-Induced Myocardial Perfusion Heterogeneity by Atenolol and Other Cardioselective β-Adrenoceptor Blockers: A Crossover Myocardial Perfusion Imaging Study

Abstract: Little is known about the effect of chronic b-blockade on adenosine actions. We sought to investigate the effect of oral b-blockers on the presence, extent, and severity of myocardial perfusion abnormality induced by adenosine in patients with coronary artery disease. Methods: In this crossover study, 45 male patients with coronary artery disease on b-blocker therapy with atenolol, bisoprolol, or metoprolol underwent adenosine myocardial perfusion imaging both on and off b-blockade in a random order on separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…However, b-blockers are generally not used with coronary artery calcium scoring. Additionally, it has been shown that the extent and severity of MPI abnormalities are reduced in patients under the effects of b-blockers (31,32). Stair-step artifacts are eliminated on 320-slice scanners wherein the entire heart volume is covered in 1-2 heartbeats (13,28), as well as with the prospectively triggered high-pitch acquisition (FLASH mode [fast-pitch spiral CT]), which requires a fraction of 1 heart beat (approximately 250 ms) for the CTA acquisition (135).…”
Section: Low-ma Imaging With Iterative Reconstruction Algorithmsmentioning
confidence: 99%
“…However, b-blockers are generally not used with coronary artery calcium scoring. Additionally, it has been shown that the extent and severity of MPI abnormalities are reduced in patients under the effects of b-blockers (31,32). Stair-step artifacts are eliminated on 320-slice scanners wherein the entire heart volume is covered in 1-2 heartbeats (13,28), as well as with the prospectively triggered high-pitch acquisition (FLASH mode [fast-pitch spiral CT]), which requires a fraction of 1 heart beat (approximately 250 ms) for the CTA acquisition (135).…”
Section: Low-ma Imaging With Iterative Reconstruction Algorithmsmentioning
confidence: 99%
“…On the other hand, a significant impact of beta blockers on adenosine MPI has been demonstrated in a prospective study 12. All the cited studies related to MPI in SPECT technique.…”
Section: Introductionmentioning
confidence: 99%
“…Despite maximal vasodilation by pharmacologic vasodilators, an interaction of cardiac medications such as beta blockers, calcium blockers, and nitrates has been suggested in several studies 8-12. Current guidelines recommend temporarily discontinuing beta blockers before stress testing 13,14…”
Section: Introductionmentioning
confidence: 99%
“…to obtain summed difference scores (SDSs). An SSS of 4 or more was considered abnormal, and an SDS of 2 or more was considered to represent clinically relevant ischemia (21)(22)(23). In addition, segments 1, 2, 7, 8, 13, 14, and 17 were assigned to the left anterior descending territory; segments 3, 4, 9, 10, and 15 to the right coronary artery territory; and segments 5, 6, 11, 12, and 16 to the left circumflex territory to allow vessel-based comparison.…”
Section: Spect Data Analysismentioning
confidence: 99%